A system to support the transparency of consumer credit offers - Bożena Frączek (Journal of Risk and Financial Management, 2020)
The development of financial markets and the low level of financial literacy does not facilitate consumer protection. A significant problem is the lack of information or unclear information regarding financial offers, including consumer credit. Financial protection for consumers can be increased by using systems that support consumers faced with a lack of transparency of consumer credit offers. The theoretical objective of the research is to identify the completeness of information allowing for verifying the annual percentage rate (APR) in the consumer credit offers presented and compared on websites of financial intermediaries and banks as well as the identify of APR calculation methods. After analysis of different credit offers (document analysis), a prototype of the system regarding credit costs measured at the appropriate interest rates (APR and AER) calculated in the correct manner was created. This may facilitate practices for informing consumers about the characteristics of consumer credit and at the same time support the implementation of the concept of responsible lending. The system developed uses a computer to simulate human thinking and to augment it with artificial intelligence. It facilitates the elimination the behavioral biases during the taking of financial decisions, which are the result of a low level of financial literacy.
Keywords: 330; consumer credit/loan; deficit of financial information; financial consumer protection; annual percentage rate; APR; annual effective rate; AER; periodic rate